2015
DOI: 10.4238/2015.october.28.3
|View full text |Cite
|
Sign up to set email alerts
|

Significant interaction of APOE rs4420638 polymorphism with HDL-C and APOA-I levels in coronary heart disease in Han Chinese men

Abstract: ABSTRACT. Apolipoprotein E (APOE) is recognized for its importance in lipoprotein metabolism and cardiovascular disease. We evaluated the association between APOE rs4420638 genotypes and circulating lipid concentrations along with the risk of coronary heart disease (CHD). We conducted a case-control study involving 1508 individuals to investigate the contribution of rs4420638 to the risk of CHD in Han Chinese. In addition, we performed a meta-analysis to evaluate the association between rs4420638 and CHD in Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Coronary artery disease is a complex disease that is affected by genetic and environmental factors. Most genes can affect lipid metabolism in the body, followed by the development of atherosclerosis [10,11,12,13,14,15,16]. Some studies have found that cardiovascular diseases such as coronary heart disease have a strong genetic basis, demonstrated by family associations and degrees of genetic influence as high as 40–50% [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery disease is a complex disease that is affected by genetic and environmental factors. Most genes can affect lipid metabolism in the body, followed by the development of atherosclerosis [10,11,12,13,14,15,16]. Some studies have found that cardiovascular diseases such as coronary heart disease have a strong genetic basis, demonstrated by family associations and degrees of genetic influence as high as 40–50% [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Gender disparity has been found in APOE-related cardiovascular disease (27). In the previous studies, we have shown that CHD risk was gender-dependent in the Han Chinese and that APOE rs4420638 polymorphism was significantly associated with increased CHD risk in male Han Chinese (28). This observation might be explained by the differences of hormonal profiles, smoking status, alcohol-drinking, occupation, and dietary habits between males and females (29,30).…”
Section: Discussionmentioning
confidence: 81%
“…The rs4420638 which is located in the APOE-APOC1-APOC4-APOC2 cluster showed a protective effect on LDL-cholesterol levels [ 28 ]. The rs4420638 was also responsible for risk of coronary heart disease of Asian population [ 29 ]. The association of LPL with lipid variables and coronary artery disease has been reported many times [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%